2013
DOI: 10.1016/j.energy.2013.03.049
|View full text |Cite
|
Sign up to set email alerts
|

Effects of relative volume-ratios on dynamic performance of a direct-heated supercritical carbon-dioxide closed Brayton cycle in a solar-thermal power plant

Abstract: The effect of the relative hot-to-cold side volume-ratios on dynamic characteristics of a closed Brayton cycle (CBC) with supercritical carbon-dioxide (sCO 2) as the working-fluid is investigated in this study. The analysis of the CBC is conducted in the context of power generation in a direct-heated (no thermal-oil loop) and dry-cooled parabolic-trough solar thermal power plant, using a control-oriented model. Dynamic performance of the sCO 2 CBC with different relative volume-ratios between the hot and cold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(15 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…They concluded that the CO 2 mass-flow should be controlled in summer time. In another paper, Rajinesh Singh et al [19] studied the effect of the relative hot-to-cold side volume-ratios on dynamic characteristics of a closed Brayton cycle with supercritical carbon-dioxide as a working-fluid and showed that an increase in the hot-to-cold side volume-ratio results in a slower and gradual dynamic response. B. D. Iverson et al [20] assessed the behavior of a supercritical recompression Brayton cycle under a fluctuating thermal energy input and concluded that despite these fluctuations, the thermal mass in the system effectively enables the Brayton cycle to continue to run for short periods until the thermal input can recover.…”
Section: Introductionmentioning
confidence: 97%
“…They concluded that the CO 2 mass-flow should be controlled in summer time. In another paper, Rajinesh Singh et al [19] studied the effect of the relative hot-to-cold side volume-ratios on dynamic characteristics of a closed Brayton cycle with supercritical carbon-dioxide as a working-fluid and showed that an increase in the hot-to-cold side volume-ratio results in a slower and gradual dynamic response. B. D. Iverson et al [20] assessed the behavior of a supercritical recompression Brayton cycle under a fluctuating thermal energy input and concluded that despite these fluctuations, the thermal mass in the system effectively enables the Brayton cycle to continue to run for short periods until the thermal input can recover.…”
Section: Introductionmentioning
confidence: 97%
“…Changes in absorbed heat by the solar irradiation results in variations in mass flow rate, pressure, temperature, and the output power. In addition, to output power, mass flow (as a result of ambient condition) affects dynamic response of the cycle . Cycle specifications (configuration, applied working fluid, working condition etc.)…”
Section: Supercritical Brayton Cyclesmentioning
confidence: 99%
“…This ratio was chosen as it was shown in Ref. [27] to provide the benefit of relatively fast cycle dynamic response while also reducing the sensitivity of the cycle to fluctuations in solar heat input and ambient air temperatures.…”
Section: Closed Brayton Power Cycle Modelmentioning
confidence: 99%